2021
DOI: 10.1098/rspb.2020.2762
|View full text |Cite
|
Sign up to set email alerts
|

Spatial sampling heterogeneity limits the detectability of deep time latitudinal biodiversity gradients

Abstract: The latitudinal biodiversity gradient (LBG), in which species richness decreases from tropical to polar regions, is a pervasive pattern of the modern biosphere. Although the distribution of fossil occurrences suggests this pattern has varied through deep time, the recognition of palaeobiogeographic patterns is hampered by geological and anthropogenic biases. In particular, spatial sampling heterogeneity has the capacity to impact upon the reconstruction of deep time LBGs. Here we use a simulation framework to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 61 publications
1
29
0
Order By: Relevance
“…Different spatial biases acting on the freshwater and marine records may also variably impact different diversity estimates, dependent on the attributes of the sampled regions (Lagomarcino & Miller, 2012). For example, the species-area effect (Hallam & Wignall, 1999;Peters, 2005Peters, , 2007Hannisdal & Peters, 2011;Close et al, 2020b) may play a role in levels of marine actinopterygian biodiversity, linked to changes in sea level and associated features (Lagomarcino & Miller, 2012;Jones et al, 2021)), whereas other factors may drive freshwater actinopterygian diversity. Discrepancies in dispersal between freshwater and marine actinopterygians are also likely to have an impact.…”
Section: (B) Geographic and Spatial Biasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Different spatial biases acting on the freshwater and marine records may also variably impact different diversity estimates, dependent on the attributes of the sampled regions (Lagomarcino & Miller, 2012). For example, the species-area effect (Hallam & Wignall, 1999;Peters, 2005Peters, , 2007Hannisdal & Peters, 2011;Close et al, 2020b) may play a role in levels of marine actinopterygian biodiversity, linked to changes in sea level and associated features (Lagomarcino & Miller, 2012;Jones et al, 2021)), whereas other factors may drive freshwater actinopterygian diversity. Discrepancies in dispersal between freshwater and marine actinopterygians are also likely to have an impact.…”
Section: (B) Geographic and Spatial Biasesmentioning
confidence: 99%
“…(1) Sampling standardisation Analytical methods of sampling standardisation (Chao, 1984, p. 198;Chao & Jost, 2012;Alroy, 2017Alroy, , 2018Alroy, , 2020, which estimate species diversity based on incomplete and uneven data are invaluable when attempting to deduce real patterns of palaeodiversity from the biases acting on the fossil record (Alroy, 2010;Close et al, 2018). Since their introduction, these methods and their application continue to be refined, moving beyond temporal standardisation to spatial standardisation (Close et al, 2020a;Jones et al, 2021) and application at different scales (Close et al, 2019). Application of these methods to the Palaeozoic actinopterygian fossil record could help to tease apart genuine diversity patterns from the trends created by fossil record biases.…”
Section: Prospects For Palaeozoic Actinopterygian Diversity Studiesmentioning
confidence: 99%
“…However, this previous work did not examine dinosaur distributions in the context of palaeoclimate and therefore could not address underlying questions of dinosaur physiological diversity. In addition, although Mannion et al 42 accounted for sampling bias in their reconstructions of dinosaur diversity, it is possible that these problems are more pervasive when assessing spatial patterns (e.g., Fraser, 45 Chiarenza et al, 46 Close et al, 47 and Jones et al 48 ), and some authors have suggested that the high-latitude peak is an artifact. 49,50 Here, we re-evaluate the distribution of Mesozoic dinosaur diversity, as well as its underlying drivers, combining a nearcomprehensive global dataset of dinosaur occurrences with past climate data from the HadCM3L Earth System Model.…”
Section: Introductionmentioning
confidence: 99%
“…S9). This mechanism has also been shown to influence perceived trends in global and paleolatitudinal biodiversity (Allison and Briggs, 1993;Jones et al, 2021). While the influence of sampling bias is well documented in the fossil record (e.g., Vilhena and Smith, 2013;Close et al, 2020), it has been largely overlooked in the oxygen isotope record.…”
Section: Discussionmentioning
confidence: 99%